Internal Initiative vs External Pressure: Evidence from Halal Standard Adoption in Indonesian Food Small and Medium Industries (SMIs) - Putri, Nilda Tri; Meuthia, Meuthia; Saputra, Ikhsan Rapi; Rahmahdian S, Rini; Vanany, Iwan; Zakuan, Norhayati (UIN Sunan Gunung Djati Bandung, 2025)
This research's focal points are identifying key factors of halal food standards (HFS) in small-medium industries (SMIs) in Padang and exploring the roles of traceability systems in compliance with the halal assurance system (HAS). The sample size included 105 food SMIs in Padang through a survey using questionnaires. The study employed Structural Equation Modeling-Partial Least Square (SEM-PLS) as a data analysis technique. Results demonstrated that external pressure from government regulations and organizational commitment as part of internal initiatives significantly affected HFS adoption, whereas the latter had a stronger effect. Meanwhile, consumer pressure, industrial competition, marketing function, operational improvement, and suppliers had no significant impact. Results also exhibited that HFS adoption and traceability systems had a significant implication for compliance with HAS. The limitation lies in variables related to halal food standard adoption factors. Accordingly, future researchers have to explore the analyzed phenomenon in various research contexts. In sum, the results afford valuable information that is favorable for industries, allowing them to provide better and safer halal food products for consumers. They also indicate that the halal traceability system enables food SMIs to elevate their business and offers a vast potency for further developing halal industries in Indonesia.